Disolución del Régimen de Hacienda en la Comunidad de Tahuato, Bolívar 1954 - Jaramillo Chamorro, Shendry Fernando (2021)
This research work provides an analysis of the socioeconomic and political transformations that occurred after the two agrarian reforms in the Simiatug parish, province of Bolivar in the 1950s and 1980s, which was developed together with the historiography and ethnography of the rural indigenous - peasant communities. For the realization of this study, the community of Tahuato and the Talahua farm were taken into consideration. The methodology used was qualitative, bibliographic type, through the use of the techniques of participant observation, field notebook, and interviews that were applied to the population for the proper collection of information to the main leaders and elderly natives of the community. The agrarian reform law was one of the links for a better quality of life for the farmer, the bibliographic sources processed in it, could serve as a guide where diverse ideas of equality and improvement would be promoted. This law stipulated that the haciendas would change their way of working and, therefore, eliminate precarious work and move to a new wage structure.